Odio il Sessantotto. L’immanenza e l’insufficienza dell’anno che tutto comprende - Alteri, Luca (SocietàMutamentoPolitica, 2018)
By reflecting, in the specific of the Sixty-eight, on the dilemma between continuity of change between this year and the Seventy-seven, the Author tries to introduce a third option: the ‘77 as a necessity, after the ‘68, in order to make concrete the “giacobine” trends of the Protest. In this way, the Author reminds us how the Year of the Protest deals not only with History, but also with the Philosophy of History.